Mild drought in the vegetative stage induces phenotypic, gene expression, and DNA methylation plasticity in Arabidopsis but no transgenerational effects - Van Dooren, Tom J M (Journal of experimental botany, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology.